Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0284185115597720
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and CT/MRI findings of alveolar soft part sarcoma: a retrospective single-center analysis of 14 cases

Abstract: ASPS should be included in the differential diagnosis when a bulky, heterogeneous soft tissue mass in the trunk and the lower limbs with intense enhancement after contrast administration and prominent intra- or peri-tumoral feeders on CT or flow voids on MRI is seen, particularly in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…In this study, stripped necrosis of decentered distribution was found in a tumor with a diameter of 90 mm in 1 patient, which was consistent with a previous report [3]. The largesized decentered necrosis happened before non-necrosis happened in the center of the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, stripped necrosis of decentered distribution was found in a tumor with a diameter of 90 mm in 1 patient, which was consistent with a previous report [3]. The largesized decentered necrosis happened before non-necrosis happened in the center of the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…Intense enhancement and feeder vessels were also a commonly seen feature. Intense enhancement, presence of feeders, and multiple flow voids were the most consistent findings across many studies 4 9 10 11 12 16 ( Figs. 2 , 3 , 4 , and 5 ).…”
Section: Discussionsupporting
confidence: 64%
“…ASPS are highly vascular tumors often presenting as pulsating masses with bruits. On imaging, ASPS are usually well-circumscribed lobulated masses with nodular architecture, moderately high T1 and T2 signal intensity, and intense heterogenous contrast enhancement with central necrosis [40]. Large vessels at the periphery converging centrally, multiple flow voids, and high signal intensity on T1 are characteristic imaging features [38][39][40][41].…”
Section: Selected Sarcomas Of the Head And Neckmentioning
confidence: 99%
“…On imaging, ASPS are usually well-circumscribed lobulated masses with nodular architecture, moderately high T1 and T2 signal intensity, and intense heterogenous contrast enhancement with central necrosis [40]. Large vessels at the periphery converging centrally, multiple flow voids, and high signal intensity on T1 are characteristic imaging features [38][39][40][41]. Although the appearance is similar to other aggressive soft tissue sarcomas, ASPS should be suggested when children or young adults present with a highly vascular mass, especially with concurrent lung metastases.…”
Section: Selected Sarcomas Of the Head And Neckmentioning
confidence: 99%
See 1 more Smart Citation